Sensorimotor reaction indicators as measures of specialized training in qualified volleyball players across different roles - Shlonska, O.; Borysova, O.; Fedorchuk, S.; Gamalii, V.; Yakusheva, Y.; Zhyrnov, O.; Nagorna, V. (Journal of Physical Education and Sport, 2025)
Objective. Modern scientific research indicates that individual-typological features and the manifestation of sensorimotor reactions, of different degrees of complexity, in players of team game sports influence the success of competitive activity and form the basis of special preparedness in athletes. The aim is to determine the manifestation of sensorimotor reactions of different degrees of complexity in players, considering their game role and the relationship between the components of competitive activity and exceptional physical fitness. Material and methods. The research involved 44 qualified female athletes aged 19 to 22 years old, members of the youth national volleyball team U-22 and the volleyball team "Dobrodiy-University-SVSM", participants in the Ukrainian volleyball championship among the teams of the Super League for the 2023-2025 season. To determine the manifestation of sensorimotor reactions of different degrees of complexity (simple visual-motor reaction (SVR), simple visual-motor reaction to the beginning of the arrow movement (SVR-AM), complex visual-motor reaction (CVR), complex visual-motor reaction to a light combination of stimuli (CVR-LC), dynamic muscular endurance of the hand movement of the dominant hand (DMEH of the DA), and subdominant hand (DMEH of the SDA)), the diagnostic complex "BOS-test professional" was used. The paired Pearson's coefficient (r) was used to investigate the interrelations between indicators of special physical fitness and components of competitive activity. Results. The analysis of sensorimotor reactions in players with different roles reveals significant differences between attacking players, setters, and liberos, which is a consequence of the distinct structure of competitive activity among these players. There are the closest interrelations between the indicators of sensorimotor abilities and exceptional physical fitness of players of different game roles: for outside hitters and opposite hitters - between the manifestation of a complex visual-motor reaction and speed and power abilities (r=0.48 and r=0.83), for middle blockers - between the dynamic muscular endurance of the subdominant hand and speed abilities (r=0.62); for setters - between dynamic muscular endurance of the dominant hand and special endurance (r=0.80); for libero - between the composition of visual-motor reaction and speed abilities (r=0.58). It was also determined that the manifestation of sensorimotor reactions of qualified volleyball players of different roles significantly affects the effectiveness of their competitive activity. Conclusions. The characteristics of neurodynamic functions, among which sensorimotor reactions of varying degrees of complexity are essential, significantly influence the development of special physical abilities and the efficiency of competitive activity in qualified volleyball players of different game roles, confirming their importance in the training system of athletes in team sports. Considering the indicators of sensorimotor reactions precisely will optimize the training process for players of different roles and facilitate rational team recruitment, taking into account individual and typological characteristics.